2019
DOI: 10.3390/ijms20184443
|View full text |Cite
|
Sign up to set email alerts
|

Evans Blue Reduces Neuropathic Pain Behavior by Inhibiting Spinal ATP Release

Abstract: Upon peripheral nerve injury, vesicular ATP is released from damaged primary afferent neurons. This extracellular ATP subsequently activates purinergic receptors of the spinal cord, which play a critical role in neuropathic pain. As an inhibitor of the vesicular nucleotide transporter (VNUT), Evans blue (EB) inhibits the vesicular storage and release of ATP in neurons. Thus, we tested whether EB could attenuate neuropathic pain behavior induced by spinal nerve ligation (SNL) in rats by targeting VNUT. An intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…In the present study, intrathecal administration of p66shc siRNA-PLGA NPs decreased microglial activation in the ipsilateral spinal cord following SNL. Our and others' previous studies showed that microglia are activated distinctly, and that activated microglia lead to excessive neuroinflammation following peripheral nerve injury, which contributes to neuropathic pain and tissue damage [5,27,28,32,33,44]. In addition, in the present study, we showed that p66shc siRNA treatment decreased H 2 O 2 -induced elevation of the mRNA levels of proinflammatory mediators, including TNF-α, IL-1β, IL-6, COX2, and iNOS, in cultured HT22 cells.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In the present study, intrathecal administration of p66shc siRNA-PLGA NPs decreased microglial activation in the ipsilateral spinal cord following SNL. Our and others' previous studies showed that microglia are activated distinctly, and that activated microglia lead to excessive neuroinflammation following peripheral nerve injury, which contributes to neuropathic pain and tissue damage [5,27,28,32,33,44]. In addition, in the present study, we showed that p66shc siRNA treatment decreased H 2 O 2 -induced elevation of the mRNA levels of proinflammatory mediators, including TNF-α, IL-1β, IL-6, COX2, and iNOS, in cultured HT22 cells.…”
Section: Discussionsupporting
confidence: 75%
“…Although many underlying mechanisms, related to the onset and development of neuropathic pain, have been suggested, mitochondrial dysfunction may be one of the most important pathophysiological mechanisms of neuropathic pain [3,4]. Our and other previous studies reported that mitochondrial reactive oxygen species (ROS) levels are increased in the neuropathic spinal cord, and that removal of ROS in neuropathic pain can lead to recovery of central sensitization and hyperalgesia to normal levels [5][6][7][8]. In addition to mitochondrial functions and ROS, autophagy has been regarded as one of the most important mechanisms for understanding neuropathic pain.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The damaged tissue cells and sensory nerve endings can release a large amount of ATP after peripheral nerve injury. 41 , 42 Studies have shown that ATP activates microglial cells, induces microglial cell aggregation and proliferation, and promotes the release of a variety of proinflammatory factors and neuroactive substances. 43 45 The release of proinflammatory factors and neuroactive substances can lead to the enhancement of excitatory synaptic transmission and hyperactivity of dorsal horn neurons (central sensitization).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, extensive studies have confirmed the pivotal role of ATP in pain. Many chemicals have been used to reduce the neuroinflammatory response and subsequently alleviate neuropathic pain by decreasing ATP release, for example, the inhibitor of vesicular nucleotide transporter ( Kato et al., 2017 ; Yin et al., 2019 ) and the inhibitor of mammalian target of rapamycin ( Cui et al., 2014 ). The decrease of ATP level in the mPFC may counter nociceptive input and transmission in the CNS.…”
Section: Discussionmentioning
confidence: 99%